(untitled) (International journal of artificial intelligence, 2026)
This study examines theoretical, methodological, and practical approaches to developing solutions for problems arising in the financial and business activities of an enterprise. In modern economic conditions, enterprises face increasing financial risks, declining profitability, inefficient resource utilization, and instability in cash flows, which negatively affect their overall performance and competitiveness. The research identifies key factors influencing financial and business activity and systematizes the most common internal and external problems hindering sustainable enterprise development. Special attention is given to the role of financial analysis, strategic planning, and management tools in diagnosing problem areas and forming effective corrective measures. The paper proposes a set of organizational, financial, and economic solutions aimed at improving liquidity, financial stability, business turnover, and profitability. The study also emphasizes the importance of integrating modern financial management instruments and performance indicators into enterprise management systems. The proposed recommendations contribute to strengthening financial resilience, increasing operational efficiency, and ensuring long-term sustainable development of enterprises in a dynamic market environment.